Vanilla norashikiniana R. Go et A. Raffi sp. nov., A New Orchid Species From Peninsular Malaysia - Akmal, Raffi; Farah Alia, Nordin; Nur Ashikin, Psyquay Abdullah; Puat, Dahalan; Rusea, Go (2017)
A new species, Vanilla norashikiniana R. Go et A. Raffi, from Peninsular Malaysia is described and other aspects of interest discussed. It is so far known from a population in lower dipterocarp forests in Hutan Lipur Chemerong, Hulu Dungun, Terengganu and Hutan Simpan Semangkok, Selangor. A field key to the Peninsular Malaysian taxa (including Vanilla shenzhenica) is also provided.